Estrategia didáctica "CUENTO LO QUE SÉ" y su influencia en la comprensión de textos en el Área de Comunicación en, los niños y niñas de cinco años de la Institución. Educativa inicial Nº 299 del distrito de Nueva Cajamarca, 2009 - Pachamora Villanueva, Oiga Soledad (2010)
The present research TEACHlNG STRATEGY called "mind what" and its influence with reading comprehension in the area of communication in children five years of School Home District No. 299 New Cajamarca. Aims to improve the learning level of children and girls in reading comprehension. This quasi-experimental research design and experimental group took ESTRSTEGIA intact DIDACTIC "account what is" consisted in 10 class sessions. For the outcome evaluation was conducted in two dimensions that consisted of 10 items 5 5 literal literal deep primary results. In the pre-test is 10.36. 15.36 In the post test indicating that infants and children if they achieved the level of learning reading comprehension. For the hypothesis test was used in the study sample consisting of 22 children who were given a test by means of a test to evaluate before and after learning the level of reading comprehension by applying the AmB DIDACTIC "WHAT'S TALE" according to research design pre-experimental pretest post-test the test with a single group statistical processing and stop measurements compared by determining the student t where (te= 8.55> Tt =- 2.080), allowed to test the hypothesis. Concluding that the teaching strategy "account what is" significantly affects the learning of reading comprehension, in the area of communication in children five years of the initial school district No. 299 of Cajamarca snow.